Sanctions: Business as Usual? (Example of Russian-German Relations) - N. V. Toganova (Модернизация, инновация, развитие)
Purpose: the purpose of the article was to analyze the influence of sanctions on economic relations of Russia and Germany (on firm level and on foreign direct investments), to find out how far the changes influenced the innovation potential of Russia in the long term and also the role of political relations in the economic context.Methods: the methodological base of the research is based on general scientific methods: scientific abstraction, analysis and synthesis, generalization, system-structural analysis.Results: the author analyzes the approaches towards quantifying the sanctions influence on Russian economy and its sectors, also the author analyzes the economic relations with Germany after the sanctions (foreign direct investment, the dynamic of German companies in Russia, corporate cash flow of some German companies, import dynamic).Conclusions and relevance: the author concludes, that although in the long run the sanctions could have an enormous impact on the innovation potential, but in the short term the overall market condition, that influences the intensity of imports and modernization of equipment, plays a bigger role. In spite of sanctions after the down turn of trade and direct investments there is a growth in amount of German business and foreign direct investment. The Russian market remains important for the German companies. The German companies are seeking to strengthening their positions. An important role plays the fact, that for the Russian companies the German ones are important suppliers of commodities and machines. This demand can’t be fully satisfied by the Asian countries.